Stepping Forward in the Digital Era: The Contribution of Business Information Systems in Responding to Global Entrepreneurship Challenges - Fitriana Rakhma Dhanias; Dinda Amelia Kusumastuti; Hapsari Dian Sylvatri; Zakaria Satrio Darmawan; Bahtiar Efendi (Jurnal Minfo Polgan, 2024)
The digital era has brought about fundamental changes in the way businesses are conducted worldwide. Entrepreneurship in the global context demands adaptability and rapid innovation in facing increasingly fierce competition. This research aims to examine the contribution of business information systems in addressing the challenges of global entrepreneurship in the digital era. The research method employed is a literature review with a qualitative approach and descriptive analysis. In this context, descriptive analysis will be used to depict the findings from selected articles from Google Scholar for the period 2004-2024. The study results indicate that in this dynamic and complex digital era, Business Information Systems (BIS) have proven to be key in addressing the challenges of global entrepreneurship. Through the integration of information technology and business processes, BIS enables companies to enhance operational efficiency, respond quickly to market changes, and create innovative products and services that differentiate them from competitors. However, the adoption of BIS is not without challenges. Companies need to pay attention to data security aspects, ensure sustainability in technology usage, and overcome organizational and cultural barriers.